Traumatic avulsion and bilateral eye loss: report of two cases - Roki, Narayani; Roka, YB; Acharya, R (Nepalese Journal of Ophthalmology, 2013)
Background: The optic nerve and the globes are resistant to mild to moderate trauma and bilateral avulsion of the eyes is rare with only a few cases reported in the literature. Case: We report two cases of traumatic bilateral eye avulsion. The first case was secondary to a bear bite and was managed successfully, although the eyes were not salvageable whereas the second case which was due to physical assault expired due to associated severe head injury. Conclusion: Traumatic bilateral globe avulsion/loss is a rare complication of trauma. In developing countries like Nepal, poverty, forest encroachment activities, extensive deforestation, frequent domestic disturbances and lack of education are some of the circumstances that increase the probability of such visual injuries. Nepal J Ophthalmol 2013; 5(10): 272-274 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8743